Variants of the Bacillus subtilis LysR-Type Regulator GltC With Altered Activator and Repressor Function - Dormeyer, Miriam; Lentes, Sabine; Richts, Björn; Heermann, Ralf; Ischebeck, Till; Commichau, Fabian M. (Frontiers in Microbiology, 2019)
The Gram-positive soil bacterium Bacillus subtilis relies on the glutamine synthetase and the glutamate synthase for glutamate biosynthesis from ammonium and 2-oxoglutarate. During growth with the carbon source glucose, the LysR-type transcriptional regulator GltC activates expression of the gltAB glutamate synthase genes. With excess of intracellular glutamate, the gltAB genes are not transcribed because the glutamate-degrading glutamate dehydrogenases (GDHs) inhibit GltC. Previous in vitro studies revealed that 2-oxoglutarate and glutamate stimulate the activator and repressor function, respectively, of GltC. Here, we have isolated GltC variants with enhanced activator or repressor function. The majority of the GltC variants with enhanced activator function differentially responded to the GDHs and to glutamate. The GltC variants with enhanced repressor function were still capable of activating the PgltA promoter in the absence of a GDH. Using PgltA promoter variants (PgltA*) that are active independent of GltC, we show that the wild type GltC and the GltC variants with enhanced repressor function inactivate PgltA* promoters in the presence of the native GDHs. These findings suggest that GltC may also act as a repressor of the gltAB genes in vivo. We discuss a model combining previous models that were derived from in vivo and in vitro experiments.